Lactational programming of glucose homeostasis: a window of opportunity. Issue 2 (August 2018) - Ellsworth, Lindsay; Harman, Emma; Padmanabhan, Vasantha; Gregg, Brigid
Abstract : The window of lactation is a critical period during which nutritional and environmental exposures impact lifelong metabolic disease risk. Significant organ and tissue development, organ expansion and maturation of cellular functions occur during the lactation period, making this a vulnerable time during which transient insults can have lasting effects. This review will cover current literature on factors influencing lactational programming such as milk composition, maternal health status and environmental endocrine disruptors. The underlying mechanisms that have the potential to contribute to lactational programming of glucose homeostasis will also be addressed, as well as potential interventions to reduce offspring metabolic disease risk.